Floristic richness comparison among the Mexican states - José Luis Villaseñor; Enrique Ortiz (Revista Mexicana de Biodiversidad)
The number of native vascular plant species recorded in each of the 32 Mexican states was evaluated to identify and compare their floristic richness values and determine their floristic similarities. The floristic richness was further segregated to estimate the proportions documented for each of the 5 main biomes recognized in the country. We assumed that the floristic composition in the Mexican states follows a geographical association and that geographically close states will show assemblages defined by their floristic elements. The state of Oaxaca recorded the highest richness in all of Mexico and 3 biomes (Humid Mountain Forest, Temperate Forest, and Seasonally Dry Tropical Forest). Chiapas had the highest number of Tropical Humid Forest species, while Coahuila had the highest richness of Xerophytic Scrub species. Floristic similarities allowed the identification of well-defined groups, either when considering total floristic richness or when analyzing each of the main biomes. The floristic similarity is highly congruent between states with geographical proximity.